Novel proton conducting membranes based on copolymers containing hydroxylated poly(ether ether ketone) and sulfonated polystyrenes. Issue 34 (7th May 2017) - Luo, Tianwei; Xu, Hulin; Li, Zhong; Gao, Shuitao; Fang, Zhou; Zhang, Zeyu; Wang, Fang; Ma, Bing; Zhu, Changjin
ABSTRACT: A novel series of hydrocarbon‐based copolymers containing flexible alkylsulfonated groups and hydroxylated poly(ether ether ketone) backbones was designed and prepared as proton conducting membranes. Among the membranes, the membrane SPO3 –(PMS–PSBOS)2 with the ion exchange capacity 1.70 showed good proton conductivity at 0.137 S/cm at 80 °C, which was two times as much as that of the control membrane SPO. Further, incorporating the sulfonated graphene oxide (s‐GO) into SPO3 –(PMS‐PSBOS)2 leads to the composite membrane SPO3 –(PMS–PSBOS)2 –SGO, which exhibited higher proton conductivity compared to Nation 117 and the native membrane SPO3 –(PMS–PSBOS)2 . In addition, the composite membrane SPO3 –(PMS–PSBOS)2 –SGO showed well‐defined phase separated structures and high selectivity (1.40 × 10 5 Ss/cm 3 ), which were about three times as that of Nafion 117 (0.52 × 10 5 Ss/cm 3 ). These results suggested that these membranes are promising materials for direct methanol fuel cell (DMFC) applications. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45205. Abstract :